Implementation of ChatGPT in moulding university students’ writing / Abdul Azim Mahda ... [et al.] - Mahda, Abdul Azim; Nik Fauzi, Sheela Faizura; Dealwis, Caesar; Haris, Nurfazlina (Universiti Teknologi MARA, Kedah, 2024)
ChatGPT, an artificial intelligence (AI) language model, can potentially mould university students’ writing as part of the Computer-Assisted Language Learning (CALL) experience. The development and application of ChatGPT have significantly impacted students’ learning process. ChatGPT has gained popularity in enhancing students’ academic writing by improving structure, creativity, and overcoming writers’ block. However, concerns about overreliance, originality, and academic integrity persist. This study explores the impact of ChatGPT on university students’ writing skills by focusing on its implementation at Universiti Teknologi MARA (UiTM) Sarawak Branch through a structured questionnaire adapted from a research framework known as Unified Theory of Acceptance and Use of Technology (UTAUT) by Venkatesh et al. (2003). It identified key factors influencing students’ behavioural intentions and actual use of ChatGPT in academic writing. Findings revealed that while students appreciated ChatGPT’s ability to refine writing structure and aid creativity, concerns over academic dishonesty and the potential reduction in critical thinking and originality were significant. Although most students found ChatGPT useful for generating complex sentences and providing alternative perspectives, some were cautious about its roles in paraphrasing and grammar checks. The study revealed the need for clear ethical guidelines and policies to ensure responsible use of AI in education. Despite the small sample size, the study contributes valuable information into ChatGPT’s roles in higher education and highlights the need for further research on its long-term effects.